2014
DOI: 10.1016/j.jgeb.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nutrient media, different cytokinin types and their concentrations on in vitro multiplication of G×N15 (hybrid of almond×peach) vegetative rootstock

Abstract: The objective of this research was to assess the effects of different media i.e. Murashige and Skoog (MS) and Quoirin and Lepoivre (QL), cytokinin type i.e. 6-Benzyladenin (BA) and 6-Benzylaminopurine (BAP) and cytokinin concentration on in vitro proliferation of the G · N15 rootstock. To evaluate the effects of different media and cytokinin type, two separate experiments were conducted as factorial based on completely randomized design, and single nodes were used as explants. The results showed that MS nutrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 29 publications
2
46
0
3
Order By: Relevance
“…Plants grown on M2 medium showed the lowest shoot length (1.8 cm on average) although not statistically different from M3 medium (Table 1). For the G × N15 hybrid (almond tree × peach tree), it was similarly reported that the highest shoots length in vitro were achieved on culture media without plant growth regulators supplementation, which may be explained mainly by the cytokinin effects on boosting shoots emission, inducing plants to produce a higher number of nutrients sinks with lower individual growth and elongation (Arab et al, 2014). Additionally, cytokinins are known to reduce apical dominance and induce adventitious shoots formation from meristematic explants (Resmi & Nair, 2011).…”
Section: Culture Media and Plant Regenerationmentioning
confidence: 98%
“…Plants grown on M2 medium showed the lowest shoot length (1.8 cm on average) although not statistically different from M3 medium (Table 1). For the G × N15 hybrid (almond tree × peach tree), it was similarly reported that the highest shoots length in vitro were achieved on culture media without plant growth regulators supplementation, which may be explained mainly by the cytokinin effects on boosting shoots emission, inducing plants to produce a higher number of nutrients sinks with lower individual growth and elongation (Arab et al, 2014). Additionally, cytokinins are known to reduce apical dominance and induce adventitious shoots formation from meristematic explants (Resmi & Nair, 2011).…”
Section: Culture Media and Plant Regenerationmentioning
confidence: 98%
“…Besides, this could also be attributed to variation in the physiological condition of the plant due to time/season of explant collection. Such difference has also been reported in other plant species [26]. Further, a combination of cytokinin and auxin (2.0 mg/l BAP + 0.5 mg/l NAA) was used by Srivastava and Srivastava [8] for micropropagation of P. foetida through nodal culture.…”
Section: Axillary Shoot Proliferation From Mature Nodal Explantmentioning
confidence: 68%
“…Thus, the effect of plant growth regulators is conflicting on axillary shoot proliferation in P. foetida. These types of results could be due to the difference in the genotype of the plant and/or age of the explant [26,27]. Besides, this could also be attributed to variation in the physiological condition of the plant due to time/season of explant collection.…”
Section: Axillary Shoot Proliferation From Mature Nodal Explantmentioning
confidence: 99%
“…These magnitudes significantly differed from each other (Tukey, 0.05). This effect could be attributed to BAP, which induces cell division of somatic cells and synthesis of specific proteins (Arab et al, 2014) that lead to later formation of meristematic structures that develop in the shoots. However, the quantity of BAP is related to how much meristematic structure can be induced (Siddique and Anis, 2009).…”
Section: Resultsmentioning
confidence: 99%